"Applying" Education: A Focused Review of the 2019 American Anthropology Master's Career Survey Data. Issue 1 (25th March 2021) - Cronin, Shannon; Hawvermale, Erica M.
Abstract: This paper reports the results of the National Association for the Practice of Anthropology‐sponsored 2019 American Anthropology Master's Career Survey. Aimed at replicating the 2009 American Anthropological Association/Committee on Practicing, Applied, and Public Interest Anthropology MA Career Survey, the purpose of this new survey was to understand 1) how master's degree anthropology alumni have crafted careers, 2) what retrospective advice they have for departmental programs, and 3) whether they continue to identify with the profession. A total of 850 participants completed the survey. Parallel to the 2009 survey, applied anthropologists indicated overall satisfaction with their master's degree programs and reflected high variability in types of employment respondents hold. However, the lack of practical skills development and career preparation within master's programs were critiqued. We conclude with recommendations for anthropology programs to help better inform them of what their students need to learn in order to lead successful careers after graduation.